1988
DOI: 10.1159/000199737
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Nutritional Parameters in Patients after Colonic Polypectomy

Abstract: Breath methane and hydrogen, plasma acetate, serum selenium, vitamin A and β-carotene were measured in 47 patients from whom colonic polyps had been removed by endoscopic polypectomy between 3 months and 2 years previously. Patients were compared with 39 control subjects in whom no abnormality was detected during colonoscopy. The proportion of methane exhalers was significantly (p < 0.0005) higher in patients after polypectomy (66.0%) than in controls (28.2%). Mean plasma acetate was lower (p < 0.025) in post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In 6 of these past studies, no effect of sex on breath methane excretion was seen (McKay et al, 1985;Scheppach et al, 1988;Bond et al, 1971;Bjorneklett and Jensen, 1982;Pique et al, 1984;Kashtan et al, 1989), while in 4 others, proportionately more women were producers than men (Segal et al, 1988;Pitt et al, 1980;Hoff et al, 1986;Haines et al, 1984). No study has found men to be significantly more likely to be producers.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In 6 of these past studies, no effect of sex on breath methane excretion was seen (McKay et al, 1985;Scheppach et al, 1988;Bond et al, 1971;Bjorneklett and Jensen, 1982;Pique et al, 1984;Kashtan et al, 1989), while in 4 others, proportionately more women were producers than men (Segal et al, 1988;Pitt et al, 1980;Hoff et al, 1986;Haines et al, 1984). No study has found men to be significantly more likely to be producers.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, breath hydrogen and methane levels were similar between sexes and only weakly associated with age. To our knowledge, only one other published study attempted to measure breath hydrogen in individuals on regular diets (Scheppach et al, 1988). However, this small study used a single fasting measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary Figure 5 contains the most relevant features, which include proteins with functionalities related to CCR, such as amino acid metabolism [56], redox metabolism [57] or more generic biomarkers of bacterial proliferation [58]. Also, some specific features of adenoma, like the coenzyme F420 hydrogenase subunit beta, related to methane metabolism, enhanced in adenoma patients [41], or the chemotaxis protein methyltransferase CheR and the pilus assembly protein FimV, both related to chemotaxis and cell motility which have been described as a distinctive feature of adenomas [42], are also listed among the most relevant features. The most relevant feature, the large subunit ribosomal protein L19e, is an archaeal protein used as bad prognostic CRC biomarker [40].…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are specific features of CRC that start to appear probably in the first adenoma stages previous to the cancer. Some of them are known CRC prognostic biomarkers, such as the archaeal large subunit ribosomal protein L19e [40], while other are characteristic of the adenoma stage, like the coenzyme F420 hydrogenase subunit beta, related to methane metabolism, enhanced in adenoma patients [41] or the chemotaxis protein methyltransferase CheR, which has been described as a distinctive feature of patients with adenomas [42].…”
Section: The Most Relevant Features That Differentiate Adenomas From mentioning
confidence: 99%